The handmade and the mechanic in the Silhouettes and Phantasmagorias series by Manuela Siebert (Revista Apotheke, 2020)
This text approaches the relation established between painting and technical image in ManuelaSiebert’s production, investigating how such association interfered over the elaboration processand visuality of her works. Thus, it takes into account the making of certain paintings fromSilhuetas e Fantasmagorias series. In this set of canvas, the artist conferred to the paintingsan aspect similar to mechanically-printed image, adopting techniques and materials of designand visual communication’s field to achieve such end. Thereby, Manuela incorporated in herpictorial practice a logic close to the industrial production mode, characterized by divisionbetween project and manufacturing. Executed at pre-determined stages, the paintings showoutlines and colors which remind the impersonal and standardized images disseminated bymass media.
Keywords: Manuela Siebert; painting; technical image